Evaluation of pH and Calcium Ion Release of Calcium Hydroxide Pastes Containing Different Substances - Hungaro Duarte, Marco Antonio; Midena, Raquel Zanin; Zeferino, Marcia A.; Vivan, Rodrigo Ricci; Weckwerth, Paulo Henrique; dos Santos, Fernando; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Elsevier B.V., 2009)
Introduction: The objective of this study was to evaluate the pH and calcium ion release of calcium hydroxide pastes associated with different substances. Methods: Forty acrylic teeth with simulated root canals were divided into 4 groups according to the substance associated to the calcium hydroxide paste: chlorhexidine (CHX) in 2 formulations (1% solution and 2% gel), Casearia sylvestris Sw extract, and propylene glycol (control). The teeth with pastes and sealed coronal accesses were immersed in 10 mL deionized water. After 10 minutes, 24 hours, 48 hours, and 7, 15, and 30 days, the teeth were removed to another container, and the liquid was analyzed. Calcium ion release was measured by atomic absorption spectrophotometry, and pH readings were made with a pH meter. Data were analyzed statistically by analysis of variance and Tukey test (alpha = 0.05). Results: Calcium analysis revealed significant differences (P < .05) for 1% CHX solution and 2% CHX gel at 10 minutes. After 24 hours, 2% CHX gel x Control and 2% CHX gel x 1% CHX solution differed significantly (P < .05). After 48 hours, there were significant differences (P < .05) for 2% CHX gel x Control and Extract x Control. No differences (P > .05) were observed among groups in the other periods. Regarding the pH, there were significant differences (P < .05) for 2% CHX gel x Control and 2% CHX gel x 1% CHX solution after 48 hours and for 2% CHX gel x Control after 15 days. In the other periods, no differences (P > .05) were observed among groups. Conclusions: All pastes behaved similarly in terms of pH and calcium ion release in the studied periods. (J Endod 2009;35:1274-1277)
Keywords: Calcium hydroxide; calcium release; Casearia sylvestris Sw; chlorhexidine; pH; propylene glycol